2012
DOI: 10.1111/j.1471-8847.2012.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

The Problematization of Medical Tourism: A Critique of Neoliberalism

Abstract: The past two decades have seen the extensive privatisation and marketisation of health care in an ever reaching number of developing countries. Within this milieu, medical tourism is being promoted as a rational economic development strategy for some developing nations, and a makeshift solution to the escalating waiting lists and exorbitant costs of health care in developed nations. This paper explores the need to problematize medical tourism in order to move beyond one dimensional neoliberal discourses that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 6 publications
(8 reference statements)
0
28
0
15
Order By: Relevance
“…It has been suggested that medical tourism Medical Tourism in the Caribbean can positively impact public healthcare through increased access to medical technology (21), a trickle down from foreign exchange that will be re-invested into public health systems (4), and the increased availability of specialists (18). Conversely, negative impacts may include a diminishing attention to public healthcare as a result of optimism toward the high-tech medicine industry, seen as being associated with development and first-world medical practices (21), the growth of a two-tiered health system (18), strain on health human resources (16), and the need to increase public healthcare capital in order to provide higher salaries to retain workers (17).…”
Section: Public Healthcarementioning
confidence: 99%
“…It has been suggested that medical tourism Medical Tourism in the Caribbean can positively impact public healthcare through increased access to medical technology (21), a trickle down from foreign exchange that will be re-invested into public health systems (4), and the increased availability of specialists (18). Conversely, negative impacts may include a diminishing attention to public healthcare as a result of optimism toward the high-tech medicine industry, seen as being associated with development and first-world medical practices (21), the growth of a two-tiered health system (18), strain on health human resources (16), and the need to increase public healthcare capital in order to provide higher salaries to retain workers (17).…”
Section: Public Healthcarementioning
confidence: 99%
“…Many articles reveal the ethical dilemmas and potential unintended consequences – as well as the blurred definitional and operational boundaries – of short-term medical missions [24,25], global health electives [26,27], and medical volunteer trips [28–32]. Others seek to delineate qualities of effective global health partnerships [33], create principles and codes of ethical engagement [19,34–39] that may guide the creation of ethically sound and successful partnerships, or facilitate the improvement of existing ones [40].…”
Section: Introductionmentioning
confidence: 99%
“…The apartheid government, who came into power in 1948, considered healthcare a private responsibility, with the exception of those who could not afford it (Coovadia et al, 2009). By 1960, approximately 80% of the white population had invested in medical aid schemes (Söderlund et al, 1998). The demand for high quality healthcare, over and above the basic primary services offered at public hospitals, resulted in the development of a large private medical sector.…”
Section: Introductionmentioning
confidence: 99%
“…Asia currently boasts the top three major global medical tourism destinations, namely, India, Singapore and Thailand (Crush, 2012). More specifically, the development of medical tourism as an economic development strategy in India is argued to have resulted from neoliberalisation of the economy and related efforts to reduce public expenditure and to open the Indian economy for foreign investment (Chee, 2010;Smith, 2012). From the early 1980s, India developed policies to actively promote the transition from a public healthcare system to the current predominantly privatised system (Chaudhry et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation